2007
DOI: 10.1295/polymj.pj2006146
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Anionic Polymerization of Polybutadienyl Lithium in Benzene: An Osmotic Effect on Propagation Process

Abstract: ABSTRACT:The kinetics of the polymerization (propagation) process of protonated polybutadienyllithium (hPB) in a nonpolar solvent, deuterated benzene (dBz), was examined with 1 H NMR. An oligomeric, deuterated butadienyllithium (oBLi) was utilized as an initiator in order to avoid a contamination of the initiation process to the NMR data. The hPBLi chains mostly formed aggregate with an average aggregation number f ¼ $ 4 through Li at their ends. The residual monomer fraction ðtÞ did not rigorously exhibit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Micellization plays an important role in polymerization reaction kinetics, because only dissociated free living anions are believed to be active species for the propagation reaction. [33][34][35][36][37] Thus the precise aggregation number m, the association constant (or the free energy of micellar formation), and the structure of the reversed micelle formed by polymer living anions are prerequisite to the profound understanding of the anionic polymerization.…”
Section: Polymer Living Anions In a Non-polar Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…Micellization plays an important role in polymerization reaction kinetics, because only dissociated free living anions are believed to be active species for the propagation reaction. [33][34][35][36][37] Thus the precise aggregation number m, the association constant (or the free energy of micellar formation), and the structure of the reversed micelle formed by polymer living anions are prerequisite to the profound understanding of the anionic polymerization.…”
Section: Polymer Living Anions In a Non-polar Solventmentioning
confidence: 99%
“…Recently, Oishi et al 37 investigated the kinetics of living anionic polymerization for butadiene in deuterated benzene (a poor solvent for PB) by 1 H NMR. They observed nonsingle-exponential decays of the monomer concentration [M] during the propagation reaction, and the deviation from the single exponential decay was enhanced by addition of inert deuterated PB.…”
Section: Polymer Living Anions In a Non-polar Solventmentioning
confidence: 99%
“…Furthermore, the decay was retarded in the presence of chemically inert, neutral (non-anionic) PB chains. 25 These results unequivocally indicated that the conventional molecular picture, shown in Scheme 1 and eq 3, does not accurately hold for the PBLi/Bz systems.…”
mentioning
confidence: 91%
“…25 The residual monomer fraction ðtÞ was found to exhibit the single-exponential decay only in the early stage of propagation where ðtÞ > 10%, and the decay of ðtÞ became slower in the late stage. 25 (This nonsingle-exponential behavior was not observed in the previous studies [1][2][3][4][5]8,9,13,14 simply because these studies traced ðtÞ only in the early stage.) Furthermore, the decay was retarded in the presence of chemically inert, neutral (non-anionic) PB chains.…”
mentioning
confidence: 92%
See 1 more Smart Citation